FURTHER STUDY ON THE VERTICAL DISTRIBUTION OF ORGANIC CONSTITUENTS IN AN ANTARCTIC LAKE : LAKE VANDA (Ninth Symposium on Polar Biology) - マツモト, ゲンキ; ワタヌキ, クニヒコ; トリイ, テツヤ; MATSUMOTO, Genki I.; WATANUKI, Kunihiko; TORII, Tetsuya (National Institute of Polar Research, 1987)
P(論文) Total organic carbon (TOC), dissolved organic carbon (DOC), and organic constituents (hydrocarbons, fatty acids and hydroxy acids) in the particulate matter (≧O.6 μm) and sediment sample of Lake Vanda in southern Victoria Land of Antarctica were studied to elucidate their features in relation to stratification of lake water and microbial distribution. The TOC and DOC concentrations increased with depth and reached the maximum values of 48 and 38 mgC/l, respectively, in the bottom water (69.0 m). The contents of particulate fatty acids between depths of 5.0 and 50.0 m were near constant but increased abruptly from a depth of 52.5 m and attained the maximum value of 130 μg/l at a depth of 57.5 m, then decreased to the bottom. This fatty acid profile probably reflects the distribution of photosynthetic plankton in the lake. Vertical distribution of branched fatty acids in the water column is consistent with that of bacterial population. Hydrocarbons were found only in the bottom water (67.5 and 69.0 m) and the sediment. The most dominant hydrocarbon was 2,6-dimethylhexadecane (tentatively identified) in all the samples, along with the abundance of long-chain n-saturated fatty acids and 3-hydroxy acids (≧C_<20>) in the sediment sample, indicating the presence of unknown microorganisms, such as fungi and bacteria in the lake bottom. The high TOC and DOC concentrations in the bottom water imply the concentration of refractory organic matter over a long period of time after degradation of labile organic constituents. departmental bulletin paper